Local and regional controls of phylogenetic structure at the high-latitude range limits of corals. Issue 1861 (23rd August 2017) - Sommer, Brigitte; Sampayo, Eugenia M.; Beger, Maria; Harrison, Peter L.; Babcock, Russ C.; Pandolfi, John M.
Abstract : Understanding how range-edge populations will respond to climate change is an urgent research priority. Here, we used a phylogenetic community ecology approach to examine how ecological and evolutionary processes shape biodiversity patterns of scleractinian corals at their high-latitude range limits in eastern Australia. We estimated phylogenetic signal in seven ecologically important functional traits and conducted tests of phylogenetic structure at local and regional scales using the net relatedness (NRI) and nearest taxon indices (NTI) for the presence/absence and abundance data. Regional tests showed light phylogenetic clustering, indicating that coral species found in this subtropical-to-temperate transition zone are more closely related to each other than are species on the nearby, more northerly Great Barrier Reef. Local tests revealed variable patterns of phylogenetic clustering and overdispersion and higher than expected phylogenetic turnover among sites. In combination, these results are broadly consistent with the hierarchical filtering model, whereby species pass through a regional climatic filter based on their tolerances for marginal conditions and subsequently segregate into local assemblages according to the relative strength of habitat filtering and species interactions. Conservatism of tested traits suggests that corals will likely track their niches with climate change. Nevertheless, high turnover of lineages among sites indicates that range shifts will probably vary among species and highlights the vulnerability and conservation significance of high-latitude reefs.